Strategic Management Research Trends In The Creative Industries: A Bibliometric Approach - Ridwan Harun, Andy Suryani, Nurzaitu Afia, Vervasia Yohana Delima, (Pascasarjana STIE Amkop Makassar, 2024)
The creative industry plays an important role in the global economy and is growing rapidly, especially in the digital era which is characterized by technological advancements and innovation. This study aims to analyze research trends in strategy management in the creative industry using a bibliometric approach. This approach allows for the exploration of publication patterns, collaborations, and research dynamics over time. Using VOSviewer software, the study identified 229 selected publications from the Dimensions database with the keywords